The Relationship between Nutritional Status and Menstrual Cycle among Medical Students at Ahmad Dahlan University - Putri Dangga, Vathana Az Zahra; Putri, Rachma Greta Perdana; Rahmatullah, Irfan (E-Jurnal Medika Udayana; Vol 13 No 4 (2024): E-Jurnal Medika Udayana, 2024)
Menstruation is the monthly shedding of the functional layer of the endometrium in the uterus that occurs when ovulation is not followed by fertilization. Menstrual irregularities occur due to hormonal disturbances caused by stress, excessive exercise, medication use, approaching menopause, eating disorders, and nutritional status such as underweight and obesity. Nutrition refers to the nutrients present in food that are required by the body to obtain energy for daily activities. Nutritional problems arise from an imbalance between the nutrients consumed and those needed by the body. To examine the relationship between nutritional status and menstrual cycles in students of the Faculty of Medicine, Ahmad Dahlan University, a research study was conducted using an observational analytical method with a cross-sectional approach. The research sample consisted of 131 students. Statistical analysis using chi-square analysis showed a p-value of 0.001, which is smaller than ? = 0.05. From these results, it can be concluded that there is a relationship between body mass index and upper arm circumference with the menstrual cycles of students in the Faculty of Medicine, Ahmad Dahlan University, while there is no relationship between waist circumference, waist-to-hip ratio, subcutaneous fat, and menstrual cycles in students of the Faculty of Medicine, Ahmad Dahlan University.